2006
DOI: 10.1510/icvts.2005.120352
|View full text |Cite
|
Sign up to set email alerts
|

The Carpentier-Edwards Perimount Magna aortic xenograft: a new design with an improved hemodynamic performance

Abstract: This study compares the implantation characteristics and the hemodynamic performance of the new Carpentier-Edwards Perimount Magna (CEPM) xenograft with those of the standard Perimount (CEPS) valve in the aortic position. Eighty consecutive patients surviving an aortic valve replacement with either the CEPS valve (n=40) or the CEPM prosthesis (n=40) in the supra-annular position were retrospectively reviewed. One year follow-up was complete and hemodynamic performance assessed by Doppler echocardiography. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 11 publications
3
27
1
Order By: Relevance
“…Dalmau et al reported superior hemodynamic performance and a lower incidence of PPM with the CEP Magna than with the CEP valve. 9 EOAs were reported at 1.58±0.29 cm 2 (5 patients) for the 19-mm Magna prosthesis and 1.28±0.13 cm 2 (9 patients) for the standard 19-mm CEP prosthesis. 8 Botzenhardt et al reported superior hemodynamics with the 19-mm Magna bioprosthesis, with a mean LVAo-PG of 11.9 mmHg and EOA of 1.65 cm 2 (4 patients).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Dalmau et al reported superior hemodynamic performance and a lower incidence of PPM with the CEP Magna than with the CEP valve. 9 EOAs were reported at 1.58±0.29 cm 2 (5 patients) for the 19-mm Magna prosthesis and 1.28±0.13 cm 2 (9 patients) for the standard 19-mm CEP prosthesis. 8 Botzenhardt et al reported superior hemodynamics with the 19-mm Magna bioprosthesis, with a mean LVAo-PG of 11.9 mmHg and EOA of 1.65 cm 2 (4 patients).…”
Section: Discussionmentioning
confidence: 95%
“…The reported EOA of 1.58 cm 2 , however, derived from a study of only 5 patients given a 19-mm Magna valve. 9 Some authors reported clinical and hemodynamic results after AVR with a 19-mm Carpentier Edwards Perimount prosthesis, which was the predecessor of the CEM valve. Sakamoto et al found significant improvements in pressure gradient and LVMI as well as an 18% prevalence of PPM after AVR with the 19-mm pericardial bioprosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Pressure gradients of the Magna, the Mosaic, and the Soprano are in accord with findings of other groups. 1,[3][4][5][6]8,13,14,20,22,[25][26][27][28][29][30][31] There are preliminary in vivo hemodynamic data available regarding the Mosaic Ultra 10 and only 1 in vivo evaluation of the Epic, which was published previously by our group. 4 The in vitro data concerning hemodynamic gradients of the Epic and the Ultra correspond well with our results.…”
Section: Mean Pressure Gradientsmentioning
confidence: 99%
“…1,3,6,8,[25][26][27] The annulus diameter is used in 5 of the 7 in vivo studies as a comparing parameter (online supplemental Table 4). The hemodynamic gradients are low for all annulus sizes; the lowest gradients were described by Botzenhardt in patients with an annulus diameter of 22 to 23 mm (7.3 mm Hg) 27 and the highest in patients with an annulus diameter of 18 to 22 mm (13.2 mm Hg).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There was no significant difference in LVMI regression in Group M (30.2 g/m 2 ± 21.1 g/m 2 ) and Group T (33.0 g/m 2 ± 23.7 g/m 2 ) in the mid-term period and (p=0.77; Figure 3). Dalmau et al [8] compared outcomes after the implantation of Mosaic ® and Magna bioprostheses in a randomized study of 86 patients; the Magna bioprosthesis group had a lower mean LVAo-PG (17.1 mmHg vs. 10.2 mmHg) and larger AVA (1.69 cm 2 vs. 1.99 cm 2 ) after 1 year than the Mosaic ® bioprosthesis group; however, no significant difference in LVMI regression was observed. They concluded that small variations in prosthetic hemodynamics may not be important for LVMI regression.…”
Section: Discussionmentioning
confidence: 99%